Cross-border interconnection of electrical power markets and the need for policy coordination - Jara Caytuiro, Fabiola (2018)
The interconnection of two power grids creates a need for new regulation policies to govern it, as many factors are involved when two markets become interconnected and the policies of each country are designed only for its internal power market. It is therefore necessary to find the best mechanism for interconnecting both markets, which will also ensure that both countries share the benefits and costs. Issues like the contribution of large hydroelectric plants with reservoirs, the implementation of unconventional renewable energy sources and the effect of both on the complementarity and integration of cross-border power markets; all are problems that have no general solution and have to be solved for each particular case.